Legal challenges in the new digital age - López Rodríguez, Ana M. (Brill Nijhoff, 2021)
[This book] "addresses a wide range of legal issues related to emerging technologies. These technologies pose prominent legal challenges, in particular, how to wedge new phenomena into old frameworks; whether we can and should delegate responsibilities to technologies and how to cope with newly created powers of manipulation"--